George Perry (c.1718–1771): industrialist, cartographer and naturalist. Issue 1 (April 2022) - Leach, Stephen; Torrens, Hugh S.
Abstract : George Perry ( c .1718–1771) is known for his involvement in the development of the iron and engineering industries of Coalbrookdale, Ironbridge Gorge, Shropshire and Liverpool, and also for his ambition to publish a history together with new maps of Liverpool. In 1758, Perry's best known work, A description of Coalbrookdale in the County of Salop, with two perspective views thereof was published. The aforementioned views, produced in collaboration with Thomas Smith of Derby (1720–1767), are two of the earliest examples of industrial landscapes. Perry also pursued interests in geology and natural history. He maintained a correspondence and exchanged specimens of fossils with, among others, Emanuel Mendes da Costa (1717–1791), Thomas Pennant (1726–1798) and Gustavus Brander ( c .1719–1787). His work on the history of Liverpool was absorbed into An essay towards the history of Leverpool drawn up from papers left by the late Mr. George Perry, and from other materials since collected by William Enfield (1773). His son, George Perry (1771–1823), was the author of Conchology, or the natural history of shells (1811). We record Perry's busy life and career and attempt to give due weight to his several different interests.